Beragam Perilaku Migrasi Tenaga Kerja pada Daerah Tertinggal di Jawa Timur Melalui Pendekatan Hedonic - Armoyu, Mohammad (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2015)
This paper is a study to analyze the linkage of the phenomenon of migration and its impact on families and the regions they left behind. This study measured factors (push factor) and pull factors (pull factor) labor to move to the destination through the framework of the hedonic approach (hedonic approach). This study uses econometric models that are multiple choice models as tools to map the labor mobility trends using logistic multinominal approach. The study was conducted in nine underdeveloped areas, namely Ngawi, Bojonegoro, Tuban, Lamongan, Nganjuk, Bangkalan, Sampang, Pamekasan and Sumenep. Multinominal logistic model estimation results indicate that all variables in the model have a significant influence on decision making migrants.